2011
DOI: 10.1371/journal.pone.0021703
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Engage Complement and Complement Receptor Bearing Innate Effector Cells to Modulate Immune Responses

Abstract: Infusion of human third-party mesenchymal stromal cells (MSCs) appears to be a promising therapy for acute graft-versus-host disease (aGvHD). To date, little is known about how MSCs interact with the body's innate immune system after clinical infusion. This study shows, that exposure of MSCs to blood type ABO-matched human blood activates the complement system, which triggers complement-mediated lymphoid and myeloid effector cell activation in blood. We found deposition of complement component C3-derived fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(137 citation statements)
references
References 34 publications
2
135
0
Order By: Relevance
“…100 Stromal cells may also be used for chronic GVHD, but they should probably be used before fibrosis occurs. 101 Stromal cells have a profound effect on coagulation, 18,20 which partly explains their effectiveness in stopping major hemorrhages. 90,102,103 BM must be accessed by aspiration, and this source of MSCs has been challenged by MSCs from adipose tissue, umbilical-cordderived MSCs and stromal cells from the placenta-such as DSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…100 Stromal cells may also be used for chronic GVHD, but they should probably be used before fibrosis occurs. 101 Stromal cells have a profound effect on coagulation, 18,20 which partly explains their effectiveness in stopping major hemorrhages. 90,102,103 BM must be accessed by aspiration, and this source of MSCs has been challenged by MSCs from adipose tissue, umbilical-cordderived MSCs and stromal cells from the placenta-such as DSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although no acute toxicity has been reported, the coagulation system is activated 18,20 and there is a concern regarding pulmonary embolism. 104 Patients treated with stromal cells need to be followed closely for the possible risk of tumor formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we and others have demonstrated that in vitro propagated MSCs spontaneously activate complement upon contact with blood, 15,16 a process in which pre-existing antibodies are integrally involved, the underlying mechanism remains unclear. N-Glycolylneuraminic acid (Neu5GC) is a sialic acid molecule found on the cells of most mammals (except humans), and almost all humans develop anti-Neu5GC antibodies due to exposure to Neu5GC from different sources, including animal meat consumption.…”
Section: N-glycolylneuraminic Acid Is Present On In Vitro Propagated mentioning
confidence: 93%
“…Data in Table 1 are in part summarized in (Chamberlain et al, 2008;Hall et al, 2006;Martino and Pluchino 2006;Pluchino et al, 2009b;Rojewski et al, 2008;Uccelli et al, 2008;Yuan et al, 2011). (Cusimano et al, 2012;Jaderstad et al, 2010) aracrine IDO-kynurenine MSCs (h) T cells, DCs T cell apoptosis, inhibition of antigen presentation (Lanz et al, 2010;Matysiak et al, 2008Matysiak et al, , 2011Meisel et al, 2004;Plumas et al, 2005 Bonnamain et al, 2012;Chabannes et al, 2007;Moll et al, 2011) Paracrine VEGF NPCs Microglia/macrophages Inhibition of microglial activation, proliferation and phagocytosis (Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine LIF NPCs Th17 cells Inhibition of Th17 cell differentiation (Cao et al, 2011;Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine Galectins MSCs/NPCs T cells Inhibition of T cell proliferation (Gieseke et al, 2010;Sioud 2011;Yamane et al, 2010Yamane et al, , 2011 Endocrine/Paracrine TSG-6 MSCs Macrophages Inhibition of macrophage activation, proliferation and phagocytosis (Fisher-Shoval et al, 2012;Lee et al, 2009;Roddy et al, 2011) EVs miR transfer MSCs/NPCs Multiple Post-transcriptional regulation (Bruno et al, 2009;Chen et al, 2010;…”
mentioning
confidence: 99%